A Study Of The Prevalence, Severity And Treatment Of Dysmenorrhoea In Medical And Nursing Students - KIRAN B,; TASNEEM SANDOZI,; AKILA L,; ANANYA CHAKRABORTY,; MEHERBAN,; R JAMUNA RANI, (International Journal of Pharma and Bio Sciences, 2012)
To study the prevalence, severity and treatment of dysmenorrhoea in medical and nursing students. A total of 401 and 97 students from SRM University, Chennai and Vydehi Institute of Medical Sciences and Research Center, Bangalore respectively were enrolled in this study. In Chennai 306 students gave a history of dysmenorrhoea giving a prevalence of 76.30%. 57.1% had severe and 19.20% had mild dysmenorrhoea. All the students enrolled in Bangalore presented with a history of dysmenorrhoea, 73.19% with severe and 26.80% mild dysmenorrhoea. Allopathic treatment was taken by 33 and 37.11%, home made remedies by 6.20 and 2.06% and ayurvedic medicines by 0.98 and 1.03% by Chennai and Bangalore students respectively. Homeopathic treatment was taken by 2.28%students in Chennai only. It is important to spread awareness about the causes and treatment of dysmenorrhoea to avoid undue sufferings causing absenteeism from work and studies.